Avoiding Complications of Microtia and Otoplasty - Romo, Thomas; Baratelli, Roxana; Raunig, Hermann (Facial Plastic Surgery, 2012)
Congenital ear surgery constitutes one of the most challenging reconstructive procedures in plastic surgery secondary to the complex architecture of the auricle and the multiple factors involved in the reconstructive techniques. The most common complications encountered during microtia repair and otoplasty are described. Emphasis is placed on preventing these complications.
Keywords: otoplasty; microtia; complications; prevention